219k views
14 votes
I need help with this​

I need help with this​-example-1

1 Answer

4 votes

Answer:

We conclude that:


(x+2)/(x+4)-(x-1)/(x+6)=(5x+16)/(\left(x+4\right)\left(x+6\right))

Explanation:

Given the expression


(x+2)/(x+4)-(x-1)/(x+6)

Least Common Multiple of x+4, x+6: (x+4) (x+6)

Adjusting fractions based on the LCM


=(\left(x+2\right)\left(x+6\right))/(\left(x+4\right)\left(x+6\right))-(\left(x-1\right)\left(x+4\right))/(\left(x+6\right)\left(x+4\right))

since the denominators are equal, combine the fractions:


(a)/(c)\pm (b)/(c)=(a\pm \:b)/(c)

so the expression becomes


=(\left(x+2\right)\left(x+6\right)-\left(x-1\right)\left(x+4\right))/(\left(x+4\right)\left(x+6\right))


=(x^2+8x+12-\left(x-1\right)\left(x+4\right))/(\left(x+4\right)\left(x+6\right))


=(x^2+8x+12-x^2-3x+4)/(\left(x+4\right)\left(x+6\right))

simplify


=(5x+16)/(\left(x+4\right)\left(x+6\right))

Therefore, we conclude that:


(x+2)/(x+4)-(x-1)/(x+6)=(5x+16)/(\left(x+4\right)\left(x+6\right))

User Blanka
by
5.3k points